TECHNOLOGY’S CRITICAL ROLE IN THE ELT CLASSROOM FOR DEVELOPING STUDENTS’ LEARNING ENTHUSIASM AND ITS OUTCOME - Baharuddin, Andi Farid (UC Journal: ELT, Linguistics and Literature Journal, 2024)
In the post-COVID-19 pandemic, the technology was currently inseparable in educational sector including in the English Language Teaching (ELT) field. Teachers in the secondary school context were encouraged to adapt technology for designing material. The technology could be like computer, tab, smartphone, etc. Through these tools, the teachers could make power points, share the material to the students’ smartphone, and conduct the e-learning activity by connecting it to internet. Therefore, this article attempted to investigate 1) the critical role of technology that could help learner to follow the teaching material and 2) the challenges of online application used by students in the e-learning class. To observe the above issue, the researcher used quantitative methodology with a case study approach. To generate the quantitative data of students’ learning interest, the researcher utilized Likert Scale model from 1 to 5 scale. The result demonstrates that 1) Technology has significant role in assisting learners to follow the subject and they have varied positive perspectives toward its use in e-learning activity, 2) even though students perceived many OAs were challenging, but through WAG application, it was effective in improving their writing skill.